Challenges and support frameworks for producing high quality business research: A~case study of Lebanese scholars - Hala Khayr Yaacoub; Laurent Yacoub; Andre Hanna (Schmalenbach Journal of Business Research (SBUR), 2025)
This paper aims at exploring the contexts of academic research outputs faced by Lebanese researchers at four major Lebanese business schools. It analyzes both challenges and support mechanisms at these institutions to suggest improvements to the existing framework considering the researchers' perspectives and opinions. A~multiple case study was carried out at four major Lebanese business schools in which 14~individuals involved in research were interviewed. Thematic analysis was carried out to explore the host of challenges faced in the sphere of research output. This study may provide other institutions and researchers in the region and the developing world with a~greater insight into necessary alterations to their own research challenges and approaches.
Keywords: I 23; 650; Business Schools; Challenges; Lebanon; Research Output; Support Mechanisms